2020
DOI: 10.31580/jmis.v3i1.1452
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-Service Quality on Customer Satisfaction in Malaysia

Abstract: This study referred to E-S-QUAL model of determinant of electronic service quality in online shopping context and, the purposed of the study is to determine the impact of e-service quality on customer satisfaction. Literature supports the concept that quality of e-services are interlinked concepts and it has the linkage with the customer satisfaction as well.The data were collected from 363 undergraduate students in Universiti Teknikal Malaysia, Melaka (UTeM) by using multistage cluster sampling to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
(11 reference statements)
1
11
0
2
Order By: Relevance
“…Penelitian ini memiliki temuan bahwa tampilan situs web memiliki pengaruh yang paling signifikan terhadap kepuasan pelanggan diantara mahasiswa Universitas Bumigora di platform Shopee. Dengan demikian, ini menunjukkan aspek kualitas layanan yang sangat kuat sebagai prediktor, dimana menunjukkan kesesuaian yang besar dengan kepuasan pelanggan (San et al, 2020).…”
Section: Discussionunclassified
“…Penelitian ini memiliki temuan bahwa tampilan situs web memiliki pengaruh yang paling signifikan terhadap kepuasan pelanggan diantara mahasiswa Universitas Bumigora di platform Shopee. Dengan demikian, ini menunjukkan aspek kualitas layanan yang sangat kuat sebagai prediktor, dimana menunjukkan kesesuaian yang besar dengan kepuasan pelanggan (San et al, 2020).…”
Section: Discussionunclassified
“…Parasuraman và cộng sự 21 giải thích rằng hiệu quả là sự thuận tiện cho KH cũng như sự nhanh chóng trong việc truy cập và sử dụng trang TMĐT. Hầu hết các nghiên cứu trước đây đã chứng minh hiệu quả là một trong các yếu tố quan trọng ảnh hưởng đến SHL của KH 20,22 . Zia và cộng sự ủng hộ nhận định trên và chỉ ra rằng các doanh nghiệp nên cung cấp một trang web mà ở đó KH có thể dễ dàng sử dụng 23 .…”
Section: Khung Phân Tích Và Phát Triển Giả Thuyết Nghiên Cứuunclassified
“…Cronbach's α and composite reliability (CR) were used as criteria to determine the reliability of research variables. Although Cronbach's α was a frequent measurement used, 48 CR was the main criterion in this research considering CR does not assume the weight equality of each indicator. The result of Cronbach's α and CR value of the research variables is shown in Table 5.…”
Section: Measurement Model Evaluationmentioning
confidence: 99%